Fracture Mechanics: Inspirations from Nature (Fracture and Structural Integrity, 2014)
In Nature there are many examples of materials performing structural functions. Nature requires materials which are stiff and strong to provide support against various forces, including self-weight, the dynamic forces involved in movement, and external loads such as wind or the actions of a predator. These materials and structures have evolved over millions of years; the science of Biomimetics seeks to understand Nature and, as aresult, to find inspiration for the creation of better engineering solutions.There has been relatively little fundamental research work in this area from a fracture mechanics point of view.Natural materials are quite brittle and, as a result, they have evolved several interesting strategies for preventing failure by crack propagation. Fatigue is also a major problem for many animals and plants. In this paper, several examples will be given of recent work in the Bioengineering Research Centre at Trinity College Dublin, investigating fracture and fatigue in such diverse materials as bamboo, the legs and wings of insects, and living cells.
Keywords: Insect Cuticle